ON THE FORMATION OF FE-NI METAL IN RENAZZO-LIKE CARBONACEOUS CHONDRITES - Connolly H.C.; Huss G.R.; Wasserburg G.J. (My University, 2001)
The Fe-Ni metal within chondrites has been postulated to have originated either through condensation or as a byproduct of chondrule formation. To test these hypotheses, we studied metal in three Renazzo-like carbonaceous (CR2) chondrites from three petrographic settings: inside chondrules, on chondrule rims, and in the matrix. Abundances of Fe, Ni, Co, Cr, and P were determined in situ by electron microprobe, and those of Os, Ir, Pt, and Au were measured by a newly developed ion microprobe technique. The refractory platinum group elements Os, Ir, and Pt behave coherently in CR2 metal. They are either all enriched, all depleted, or unfractionated with respect to Fe and cosmic ratios. Metal with approximately CI Os/Fe, Ir/Fe, and Pt/Fe occur primarily in chondrule interiors. All metal grains have essentially CI values of Ni/Fe and Co/Fe. Almost all metal grains have lower-than-CI ratios of the volatile elements, Au and P. We also estimated the bulk compositions via analyses of phases and modal recombination of a subset of the chondrules whose metal we analyzed. The bulk compositions of chondrules are generally unfractionated relative to CI chondrites for elements more refractory than ~Cr but are depleted in more volatile elements. Abundances of siderophile elements correlate strongly with the metal abundance in the chondrules, which implies that siderophile depletions are due to expulsion of metal from the chondrule melts. The metal most likely originated during melting via reduction of oxides by C that was part of the chondrule precursor. During chondrule heating, molten metal efficiently extracted siderophile elements from the silicate melt. Rim metal consists of two types. One is like metal in chondrule interiors and was in the process of being expelled when the chondrules were quenched. The other shows systematic depletions in Os, Ir, and Pt relative to Fe and higher concentrations of Au and P than interior metal. This metal is attributed to recondensation from a vapor depleted in refractory siderophiles, a vapor most likely derived via evaporation from chondrules. Large, isolated matrix metal grains comprise the same two groups as rim grains and have the same origins. Bulk chondrule compositions and siderophile abundance patterns in metal indicate that the precursors of CR2 chondrules had CI-like abundances of refractory and moderately volatile elements but was likely depleted in the more volatile elements.